The Market as "God"?. Issue 1 (March 2016) - Day, Keri
Abstract: This article explores two lines of inquiry. The first is related to the production of human subjectivities in relation to market ideology and practices. What kinds of human subjectivities are produced when people worship the market as "God"? The market and its values of hyper‐competition become idols as people overly direct their energy toward earning and accumulating financial and social capital in order to find meaning and worth. Worshiping the market reflects a perverted anthropology. The second line of inquiry is related to the language of sacrifice intrinsic to both free market logic and Western Christian theology. Could Christian theology, even unwittingly, reinforce the problem of sacrifice in market logic, which justifies forms of human loss (such as chronic poverty) in order to promote long‐term economic growth and greater human wellbeing?